The flow and thermal properties of radiating magnetohydrodynamics hybrid nanofluid over an inclined plane - Nanthini Balakrishnan,; Siti Suzilliana Putri Mohamed Isa,; Nurul Syuhada Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2025)
In recent times, incorporating nanoparticles when studying the boundary layer flow has caught attention of many researchers due their promising abilities to elevate the thermal exchange within a fluid structure. In virtue of the vast applications in engineering and industrial fields, extending/compressing sheet, magnetic field and thermal radiation have been the persistently added controlling effects to the flow environment through years. Subsequently, this study investigates the flow and thermal properties of Ethylene Glycol (EG) magnetohydrodynamics hybrid nanofluid accommodating CoFe2O4 and TiO2 nanoparticles passing a slanted extending/compressing plane with thermal radiation. Employing similarity transformation, the problem’s governing equations are altered to an array of ordinary differential equations. The solver function for boundary value problem (bvp4c) provided by MATLAB software is applied to numerically solve these ordinary differential equations. The occurrence of numerical solutions for specific values of volume fraction of nanoparticles has been observed upon utilization of MATLAB. For diverse values of the parameter, the findings for flow and thermal profiles are portrayed graphically. Additionally, the influence of extending/compressing sheet rate and volume fraction of nanoparticles on the skin friction coefficient and local Nusselt number are also investigated. It has been perceived that the profiles of flow and thermal are enhanced when volume fraction of CoFe2O4 and TiO2 are increased for the extending plane case. The opposite effects in flow and thermal profiles are noticed for compressing plane case.